2022
DOI: 10.3389/fpsyg.2022.882705
|View full text |Cite
|
Sign up to set email alerts
|

Source Credibility and the Information Quality Matter in Public Engagement on Social Networking Sites During the COVID-19 Crisis

Abstract: During the coronavirus disease 2019 (COVID-19) pandemic, people use social networking sites (SNSs) to seek social support, ease the move toward the social distance, and communicate and engage with one another. However, there is growing evidence that trustworthiness and quality of information can affect individuals’ online engagement behaviors. This study proposes a theoretical model to test people’s online engagement during the COVID-19 pandemic by applying the elaboration likelihood model (ELM). Through a que… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 98 publications
0
13
0
Order By: Relevance
“…Although the SCCT theory is commonly utilized in crisis communication research, it has been revealed by scholars that it possesses constraints in assessing the variables that could affect the reputation of an organization Jamal & Abu Bakar, 2017a;Jiang et al, 2016;Ndlela & Ndlela, 2019;Shah & Wei, 2022). Organizational RSC in times of crisis can influence the overall effectiveness and efficacy of crisis response strategies, which will positively protect the reputation during a crisis (Lim & Brown-Devlin, 2021).…”
Section: The Connections: Source Credibility (Trustworthiness) Crisis...mentioning
confidence: 99%
See 4 more Smart Citations
“…Although the SCCT theory is commonly utilized in crisis communication research, it has been revealed by scholars that it possesses constraints in assessing the variables that could affect the reputation of an organization Jamal & Abu Bakar, 2017a;Jiang et al, 2016;Ndlela & Ndlela, 2019;Shah & Wei, 2022). Organizational RSC in times of crisis can influence the overall effectiveness and efficacy of crisis response strategies, which will positively protect the reputation during a crisis (Lim & Brown-Devlin, 2021).…”
Section: The Connections: Source Credibility (Trustworthiness) Crisis...mentioning
confidence: 99%
“…The Crisis response strategies in the SCCT have four dimensions: denial, diminishing, rebuilding and bolstering response strategies (Coombs, 2007a). RSC can intensify the relationships between crisis response strategies (Dominic et al, 2023;Jamal & Abu Bakar, 2017a;Shah & Wei, 2022;Tkalac Verčič et al, 2019) and protects organizational reputations (see Figure 2).…”
Section: The Connections: Source Credibility (Trustworthiness) Crisis...mentioning
confidence: 99%
See 3 more Smart Citations